STUDI KARAKTERISTIK PASIR SIURI DENGAN PENAMBAHAN BUTIRAN HALUS NONPLASTIS (STUDI KASUS FC - Chandra, Herfiya; Oktaviana, Ida Sri; Irdhiani, Irdhiani (JOURNAL TEKNIK SIPIL DAN INFRASTRUKTUR, 2013)
Physical and mechanical properties of uniform sand (Siuri sand) mixed with fine grains is not the same as pure uniform sand, and the void ratio (e) can not be considered as appropriate index to describe the microstructure changes due to the fine grains. Thus, the use of intergranular void ratio is recommended for the condition of fine content less than the threshold fine content (FC <FCth). In this article, the primary data were obtained by conducting laboratory tests, by testing the physical and mechanical properties of the mixtures. Tests were carried out on pure Siuri sand (0%), pure non-plastic fines (100%), and the mixtures with fine content variations of 10% - 90% (by weight of mixture), however, the discussion were focused on dominant coarse grain conditions which was pure Siuri sand (0%) and the mixtures with non-plastic fine composition varied as 10%, 20%, 30% and 40%. The results show that the changes in content of non-plastic fines combined with Siuri sand showed characteristic changes in a similar pattern both in physical and mechanical properties. Fines addition to Siuri sand had increased the value of some parameter (gd, gdmax, gdmin, f, dan t) and had decrease some other parameter (e, emax, dan emin) up to the 30% fine content, then the opposite occured in 40% fine content. When fine content had exceed threshold fine content (FCth) which were between 30-40%, it showed a behavior transition, from behavior of higher contribution of sand in the mixture (dominance of sands) to higher contribution of fines (dominance of fines). Â  Keywords: void ratio, intergranular void ratio, shear strength, Siuri Sand